Late colonial antecedents of modern democracy. Issue 4 (28th August 2022) - Bjørnskov, Christian; Rode, Martin
Abstract: Claims that colonial political institutions fundamentally affected the probability for democratic governance in the post-colonial period are probably among some of the most contested in institutional analysis. The current paper revisits this literature using a previously unused source of empirical information – the Statesman's Yearbook – on a large number of non-sovereign countries in the immediate aftermath of World War II. Our analysis shows that neither the size of the European population nor the existence of institutions of higher education appear to be important for the subsequent democratisation of countries decolonised during the latter half of the 20th century, while the existence of representative political bodies during the late colonial period clearly predicts the existence and stability of democracy in recent decades. Successful transplants of democracy to former colonies thus seem to crucially depend on whether recipients had time available to experiment around and adjust the imported institutions to local practices.